Penerapan Participatory Action Research dalam Edukasi Gizi Melalui Demonstrasi Pengolahan Pangan Lokal untuk Pencegahan Stunting di Bonto Perak - Widyaningsih, Yasinta Indah; Jasmin Ambas; Andi Nurzakiah Amin; Mahendri Deayu Putri; Nurfalia Harfah (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2025)
This community service program addressed persistent nutritional problems among vulnerable groups by strengthening knowledge and practical skills related to complementary feeding using local food sources. The activity aimed to enhance community awareness and behavioral readiness in preventing stunting through a Participatory Action Research (PAR) approach. The program was implemented in [insert location] and involved approximately 50 participants, including pregnant women, mothers of children under five, adolescent girls, and community health volunteers. Educational sessions were combined with a hands-on cooking demonstration of a locally adapted complementary food, Kue Lumpur, enriched with milkfish (Chanos chanos), moringa leaves, and pumpkin to increase nutrient density. Data were collected through pre-test and post-test assessments to evaluate changes in participants’ knowledge. The results demonstrated a substantial improvement, indicated by a marked increase in the proportion of participants achieving the “good” knowledge category and a notable reduction in the “poor” category. These findings show that the integration of clinical nutrition education with practical food preparation effectively enhances comprehension and promotes healthier feeding practices. Overall, the program highlights the potential of community-driven, participatory approaches to support stunting prevention efforts at the grassroots level.